Proteomic analysis of aqueous humor from primary open angle glaucoma patients on drug treatment revealed altered complement activation cascade - Adav, Sunil Shankar (2020)
Primary open angle glaucoma (POAG) is a complex disease and a leading cause of irreversible blindness, and its underlying pathophysiology remains poorly understood. Proteomic characterization of the protein composition of aqueous humor (AH) may identify prognostic candidate proteins involved in pathogenesis and progression of the disease. To delineate the possible mechanisms that lead to POAG, this study adopted state-of-art mass spectrometric technique and analyzed AH of POAG and their respective controls. In total, more than 1000 proteins were identified with false discovery rate of less than 1%. Numerous proteins of complement cascade, immunoglobulin, neuronal and amyloidogenic proteins, which were part of processes like acute-phase and inflammatory response, humoral immune and acute inflammatory response, regulation of complement activation and protein processing were identified. Proteins of complement system underwent significant changes, which correlate to pathogenic events characterizing POAG, including altered complement cascade, astrocyte activation, neural degeneration, and apoptosis. Further, protein modification such as deamidation of complement subcomponent was noted, particularly in POAG. Proteomic analysis of AH allows a better understanding of the mechanism involved in the pathogenesis of POAG.